2021
DOI: 10.1002/ase.2110
|View full text |Cite
|
Sign up to set email alerts
|

Support for using a three‐dimensional anatomy application over anatomical atlases in a randomized comparison

Abstract: Medical students spend many hours studying anatomy in order to learn to identify structures with the ultimate aim to achieve a threedimensional (3D) understanding of the body and to assimilate a large number of anatomical terms within a short period of time. The purpose is not only to understand anatomical concepts and learn the terminology but also to prepare physicians for physical examination of patients. "Learning by doing", that is, the active engagement with the objects of learning, can support this, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Technologies such as 3D dissection programs, VR, AR, and 3D printing have changed the way that anatomy is communicated (Ma et al, 2016; Papa et al, 2022; Yoo et al, 2021; Zilverschoon et al, 2022). 3D visualization technology has become more popular, and expectations are mounting as it can provide interesting experiences for students that are not possible with existing methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technologies such as 3D dissection programs, VR, AR, and 3D printing have changed the way that anatomy is communicated (Ma et al, 2016; Papa et al, 2022; Yoo et al, 2021; Zilverschoon et al, 2022). 3D visualization technology has become more popular, and expectations are mounting as it can provide interesting experiences for students that are not possible with existing methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, teaching faculties for anatomy in medical schools still prefer face‐to‐face practice using cadavers, which is considered the most effective method (Franchi, 2020; Papa et al, 2022; Wilhelm et al, 2022). Some of the very few studies that have analyzed the effects of 3D dissection programs found that 3D models of the human body were effective tools for learning human anatomy (Chang et al, 2022; Mahdy & Sayed, 2022; Zilverschoon et al, 2022). The learners in the study by McWatt (2021) placed great value on the continued use of content that enabled anatomy to be visualized in 3D.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional anatomical learning has been shown to be a more effective studying tool compared to 2D technologies. 14 Further, 3D teaching models are noninferior to cadaveric teaching, are often cheaper, and potentially more accessible. [15][16][17] Simple and even complex joint reductions can be performed out of hospital, and studies have shown the relative ease and safety of prehospital joint reductions.…”
Section: Discussionmentioning
confidence: 99%
“…That the use of anatomical models in teaching can be effective is known from medical education, in which the use of anatomical models has a longstanding tradition (Narang et al, 2021;Talairach-Vielmas, 2014). From studies in this context, it is known that three-dimensional anatomical models -whether plastic models (Smith et al, 2018) or digital threedimensional models (Haque et al, 2021;Nicholson et al, 2006;Zilverschoon et al, 2021) -can have a greater learning effect than two-dimensional representations. However, there is hardly any control group study on the effectiveness of the use of anatomical models in the context of human biology topics in general studies at primary school.…”
Section: Anatomical Models In Science Classmentioning
confidence: 99%